anonymous
  • anonymous
The sum of a geometric series is -2044. If the first term is -4 and the common ratio is 2, what is the final term in the sequence?
Mathematics
katieb
  • katieb
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
Sn = a[r^n-1]/r-1
anonymous
  • anonymous
use this and find n
anonymous
  • anonymous
Wait @Yahoo!

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
then an = a*r^(n-1)
anonymous
  • anonymous
Why @waterineyes any mistake
anonymous
  • anonymous
Sorry my mistake... Ha ha ha..
anonymous
  • anonymous
\[-2044 = -4[2^n -1]/(2-1)\]
anonymous
  • anonymous
511 = 2^n - 1 510 = 2^n
anonymous
  • anonymous
find n??
rsadhvika
  • rsadhvika
\(-2044 = -4. \frac{2^{n}-1}{2-1}\) \(-2044 = -4. (2^{n}-1)\) \(511 = 2^{n}-1\) \(512 = 2^{n}\) \(2^9 = 2^{n}\) 9=n
anonymous
  • anonymous
512
anonymous
  • anonymous
sorry 512 = 2^n
anonymous
  • anonymous
now n = 9
anonymous
  • anonymous
subs in an = a * r^(n-1)
anonymous
  • anonymous
\[\large 2^n = 512 \implies 2^n = 2^9 \implies \color{green}{n = 9}\]
anonymous
  • anonymous
an = -4 * 2^8
anonymous
  • anonymous
you can replace n here by 9 @Yahoo!
anonymous
  • anonymous
256 * -4 = -1024
anonymous
  • anonymous
lol thanks!
anonymous
  • anonymous
Welcome

Looking for something else?

Not the answer you are looking for? Search for more explanations.